1991
DOI: 10.1007/bf03347906
|View full text |Cite
|
Sign up to set email alerts
|

Follicular fluid lipoproteins in preovulatory period and their relationship with follicular maturation and progesterone production by human granulosa-luteal cells in vivo and in vitro

Abstract: Follicular fluid (FF) lipoprotein content was evaluated in an in vitro fertilization/embryo transfer and gamete--intrafallopian--transfer program and correlated to follicular and oocyte maturation. Moreover, the in vitro progesterone response of granulosa-luteal cells from 10 patients to high-density lipoprotein (HDL) and to low-density lipoprotein (LDL) was assessed. Most FFs contained only HDL. Sixteen out of 97 FFs contained also very low levels of LDL and very-low-density lipoprotein (VLDL). The presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…While the stimulation of progesterone production by HDL is consistent with a number of previously published studies (e.g. Enk et al 1987, Parinaud et al 1987, Volpe et al 1991, prior studies have all reported HDL to be less potent than LDL in increasing basal and gonadotrophin-stimulated progesterone output from human luteinized ovarian cells. To the best of our knowledge, this is the first study to report that HDL can stimulate a comparable steroid response to that elicited by LDL at the same protein concentration.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…While the stimulation of progesterone production by HDL is consistent with a number of previously published studies (e.g. Enk et al 1987, Parinaud et al 1987, Volpe et al 1991, prior studies have all reported HDL to be less potent than LDL in increasing basal and gonadotrophin-stimulated progesterone output from human luteinized ovarian cells. To the best of our knowledge, this is the first study to report that HDL can stimulate a comparable steroid response to that elicited by LDL at the same protein concentration.…”
Section: Discussionsupporting
confidence: 90%
“…Carr et al 1981, Tureck & Strauss 1982, Soto et al 1984, Golos et al 1985, the effects of HDL have varied dramatically between different studies. Initial studies found that HDL had no significant effect on progesterone synthesis in the human CL (Simpson et al 1980, Carr et al 1981, Tureck & Strauss 1982, while more recent studies have reported increased progesterone synthesis by luteinized cells treated with HDL (Enk et al 1987, Parinaud et al 1987, Volpe et al 1991, Azhar et al 1998.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triacylglycerols and fatty acids are present in the follicular fluid of numerous species and there is emerging interest in understanding how these substrates are ultimately utilised by ovarian somatic cells and oocytes for energy production. Analyses of lipoproteins in human follicular fluid in several studies corroborate that HDLs but little or no LDL or VLDL are present (Simpson et al 1980, Perret et al 1985, Volpe et al 1991, Jaspard et al 1997. Follicular fluid HDL cholesterol is positively correlated with serum HDL cholesterol (Gautier et al 2010, Valckx et al 2012, indicating that HDL particles are serum derived and passively equilibrated; however, there is no similar correlation for VLDL cholesterol in follicular fluid and serum (Gautier et al 2010).…”
Section: Fatty Acid Supply To the Cocmentioning
confidence: 98%
“…Then, LDL and its phospholipids change their bioactivity (Heery et al 1995, Marathe et al 1999, Löhrke et al 2005a. Thecal vascularization and vascular permeability increase during preovulatory development, and preovulatory follicles have been reported to contain LDL and high density lipoprotein (HDL) (Simpson et al 1980, Volpe et al 1991, Jaspard et al 1997). These lipoproteins have been shown to support synthesis of progesterone by supplying cholesterol from LDL (Bao et al 1995) but also by cholesterol-dependent and -independent actions of HDL , Ragoobir et al 2002.…”
Section: Introductionmentioning
confidence: 99%